2012
DOI: 10.1007/s00432-011-1132-8
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-mediated inhibition of RAD51 expression and homologous recombination in cancer cells

Abstract: These results demonstrate that methotrexate can affect homologous recombination repair of DNA double-strand breaks by controlling the expression of homologous recombination-related genes and suppressing the proper assembly of homologous recombination-directed subnuclear foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…We found that MTX treatment gave rise to significantly decreased RAD51 in choriocarcinoma cells, whereas the inhibitory effect was inconspicuous in MG63 cells. However, inconsistent with our results, RAD51 was reported to be dramatically suppressed by MTX in another osteosarcoma cell line HOS, perhaps due to different cell types and MTX treatment conditions 25. Our findings suggest that MTX-induced inhibition on RAD51 led to persistently unrepaired DSBs in choriocarcinoma cell, which consequently result in chemotherapeutic hypersensitivity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that MTX treatment gave rise to significantly decreased RAD51 in choriocarcinoma cells, whereas the inhibitory effect was inconspicuous in MG63 cells. However, inconsistent with our results, RAD51 was reported to be dramatically suppressed by MTX in another osteosarcoma cell line HOS, perhaps due to different cell types and MTX treatment conditions 25. Our findings suggest that MTX-induced inhibition on RAD51 led to persistently unrepaired DSBs in choriocarcinoma cell, which consequently result in chemotherapeutic hypersensitivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Besides HR, non-homologous end joining (NHEJ) is another repair pathway for DSB. There is evidence that NHEJ mutant cells are more sensitive to MTX compared to the parental ones, which is consistent with our results that MTX acts through inducing DSBs 25. However, there is evidence that the increased incidence of SPTs (hematologic malignancies, colorectal cancer, thyroid cancer, etc) after choriocarcinoma may be associated with MTX treatment 17.…”
Section: Discussionsupporting
confidence: 91%
“…To further ensure the uptake of methotrexate by Hut78 cells, we investigated the mRNA expression level of the RAD51 gene under the same condition of methotrexate treatment. RAD51 was shown as a target of methotrexate effect . Consistent with that reported, we observed significant decrease in RAD51 mRNA expression on methotrexate‐treated Hut78 cells, in a time‐dependent manner ( P < 0.05, one‐way anova ; Fig.…”
Section: Resultssupporting
confidence: 90%
“…There are fewer reports regarding the association of methotrexate with DNA repair systems. Nonetheless, methotrexate has been shown to affect the homologous recombination repair of DNA DSBs by controlling the expression of HR related genes and suppressing the proper assembly of HR recombination-directed subnuclear foci [49]. …”
Section: Discussionmentioning
confidence: 99%